Synergistic power of genomic selection, assisted reproductive technologies, and gene editing to drive genetic improvement of cattle - Maci L. Mueller; Alison L. Van Eenennaam (CABI Agriculture and Bioscience)
Abstract Genetic improvement of cattle around the globe has been, and will continue to be, an important driver of animal agriculture sustainability. There are several reproductive and molecular biotechnologies that are used in genetic improvement of cattle, and their impact on the rate of genetic progress is maximized when combined synergistically in a structured breeding program with a clear breeding objective. One of the most recently developed and increasingly popular tools, gene editing, allows animal breeders to precisely add, delete, or replace letters in the genetic code so as to influence a specific trait of interest (e.g., disease resistance), in as little as one generation. However, for gene editing to be an important factor for genetic improvement, it must integrate smoothly into conventional cattle breeding programs to maintain or accelerate rates of genetic gain. This review first summarizes the current state of key reproductive and molecular biotechnologies available for the genetic improvement of cattle, and then discusses potential strategies for effectively incorporating gene editing into cattle genetic improvement programs and methods for disseminating traits improved via gene editing. Moreover, it examines how genetic improvement strategies, including the use of gene editing, will differ depending on the cattle industry sector (i.e., dairy or beef), and the region of the world in which they are being deployed.